Effect of Processing Temperature on Antioxidant Activity of Ficus carica Leaves Extract - Bahrin, Nurlyana; Muhammad, Norhayati; Abdullah, Norazlin; Hj A Talip, Balkis; Jusoh, Samsiah; Theng, Siew Wei (Journal of Science and Technology, 2018)
Ethanol is acknowledged as a good solvent for polyphenol extraction and is safe for human consumption. Therefore, it usually used in the extraction process of plant sample. However ethanol should be evaporated to obtain pure extract of the samples. Nevertheless, temperature involved during evaporation process would affect the antioxidant activity of the plant extract. Thus, the purpose of this study was to find out the effect of temperature used during evaporation of ethanol towards antioxidant activity of Ficus carica leaves extract.Â  Dried powder of F. carica leaves were subjected to three sets of processing method which involve different temperatures: Set A involved maceration with 70% ethanol, followed by evaporation of ethanol in rotary evaporator at 60oC for 12 hours, set B involved maceration with 70% ethanol, followed by evaporation of ethanol in vacuum oven at 45oC for 12 hours, while set C involved maceration with 70% ethanol, followed by evaporation of ethanol at 25oC (room temperature) in fume chamber for 72 hours. Antioxidant activity of extracts from each set were measured using two different in-vitro assays, including scavenging abilities on 1,1-diphenyl-2-picryl-hydrazyl (DPPH) and total phenolic content (TPC). F. carica extract from set B showed the highest antioxidant power in DPPH (3.78 mg/ml) and TPC (266.96 mg GAE/g) compared to set A and C. Thus, it can be concluded that temperature of 45oC could promote the antioxidant activities, while high temperature would decrease the antioxidant abilities of F. carica leaves extract.